Analisis Kemampuan Representasi Matematis Masalah Kontekstual pada Soal Tes Kemampuan Akademik (TKA) - Nabila Wulandari; Defa Nurhafizah; Syaripah Syaripah (Universitas Ma'arif Lampung, 2026)
Mathematical representation ability is one of the important skills in mathematics learning because it helps students understand, present, and solve mathematical problems. However, many students still experience difficulties in using mathematical representations, especially in solving contextual problems in Academic Ability Test questions. This study aims to describe students’ mathematical representation abilities in solving contextual problems on Academic Ability Test questions in terms of visual, symbolic, and verbal representations. This study used a qualitative approach with a descriptive research design. The research subjects were students of class IX B at a junior high school selected using purposive sampling based on the mathematics teacher’s recommendation. The research instruments included, interview guidelines, observation sheets, and documentation (a mathematical representation ability test). Data were collected through, interviews, observations, and documentation (tests). Data analysis used the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results showed that students’ visual and symbolic representation abilities were relatively good, while their verbal representation abilities were still low. Most students were able to create visual representations and construct mathematical models appropriately, but they still had difficulties explaining the problem-solving process using written words. In addition, students tended to focus more on direct calculations rather than providing verbal explanations in solving contextual problems on academic ability test questions.